2017
DOI: 10.1089/humc.2017.125
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of AAV5 Vectors Expressing Human or Canine CNGB3 in CNGB3-Mutant Dogs

Abstract: Achromatopsia is an inherited retinal disorder of cone photoreceptors characterized by markedly reduced visual acuity, extreme light sensitivity, and absence of color discrimination. Approximately 50% of cases are caused by mutations in the cone photoreceptor-specific cyclic nucleotide gated channel beta subunit (CNGB3) gene. Studies in CNGB3-mutant dogs showed that subretinal injection of an AAV vector expressing human CNGB3, which has 76% amino acid identity with canine CNGB3, driven by a 2.1 kb human red co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Based on these proof-of-concept studies, two independent translational programs for CNGB3-ACHM were initiated. Safety data obtained in mice, dogs, and cynomolgus monkeys were published from one of the programs [90][91][92]. The studies showed acceptable safety with vectorand dose-dependent inflammation and toxicity.…”
Section: Gene Supplementation Therapy: Preclinical Studiesmentioning
confidence: 99%
“…Based on these proof-of-concept studies, two independent translational programs for CNGB3-ACHM were initiated. Safety data obtained in mice, dogs, and cynomolgus monkeys were published from one of the programs [90][91][92]. The studies showed acceptable safety with vectorand dose-dependent inflammation and toxicity.…”
Section: Gene Supplementation Therapy: Preclinical Studiesmentioning
confidence: 99%
“…Even though the inflammation resolved using steroids, only one patient of the 1 × 10 10 vg and none of the 1 × 10 9 vg cohorts developed similar adverse events, emphasizing the impact of the vector dose on ocular inflammation [ 120 ]. Several preclinical studies or clinical trials reported similar data, with what appears to be a threshold targeting inflammation at above 1 × 10 11 vg/eye [ 5 , 121 , 122 , 123 , 124 , 125 , 126 , 127 ].…”
Section: Options To Reduce Immunological Riskmentioning
confidence: 70%
“…Delivery of a human CNGB3 gene via rAAV5 vector to both Cngb3 −/− and the D262N mutant dogs showed that the vector could be targeted to the medium and long wavelength (M/L) cones via a human red cone opsin promoter and the rescue was dependent on the age of the dog and the promotor, not on the mutation type [90].…”
Section: Cngb3mentioning
confidence: 99%